2017
DOI: 10.1111/desc.12563
|View full text |Cite
|
Sign up to set email alerts
|

Atypical inter‐hemispheric communication correlates with altered motor inhibition during learning of a new bimanual coordination pattern in developmental coordination disorder

Abstract: Impairment of motor learning skills in developmental coordination disorder (DCD) has been reported in several studies. Some hypotheses on neural mechanisms of motor learning deficits in DCD have emerged but, to date, brain-imaging investigations are scarce. The aim of the present study is to assess possible changes in communication between brain areas during practice of a new bimanual coordination task in teenagers with DCD (n = 10) compared to matched controls (n = 10). Accuracy, stability and number of mirro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 70 publications
3
26
0
1
Order By: Relevance
“…Furthermore, the reduced interhemispheric cortical inhibition identified in our DCD group is consistent with the growing number of behavioral studies which have consistently found more unwanted activity of ipsilateral homologous muscles (i.e., mirror movements) during lateralized unimanual motor tasks ( 76 , 77 ) and bimanual coordination tasks ( 73 , 74 , 119 ) in DCD than TD controls. For example, during a recent finger tapping task which requires children to switch from bimanual to unimanual finger tapping, children with DCD made more additional taps of a non-cued finger when required to switch from tapping with both fingers to tapping with just one ( 119 ).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Furthermore, the reduced interhemispheric cortical inhibition identified in our DCD group is consistent with the growing number of behavioral studies which have consistently found more unwanted activity of ipsilateral homologous muscles (i.e., mirror movements) during lateralized unimanual motor tasks ( 76 , 77 ) and bimanual coordination tasks ( 73 , 74 , 119 ) in DCD than TD controls. For example, during a recent finger tapping task which requires children to switch from bimanual to unimanual finger tapping, children with DCD made more additional taps of a non-cued finger when required to switch from tapping with both fingers to tapping with just one ( 119 ).…”
Section: Discussionsupporting
confidence: 90%
“…Our neurophysiological findings are also in line with recent structural MRI work showing functional anisotropy reductions in calossal regions in children with DCD, the major communication pathway between hemispheres ( 120 ). While speculative, the decreased interhemispheric cortical inhibition of M1 activity observed here in DCD could certainly be a plausible mechanism with which to explain the reduced interhemispheric communication in individuals with DCD ( 73 ) and the greater mirror movements observed.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations